TERT de novo mutation-associated dyskeratosis congenita and porto-sinusoidal vascular disease: a case report - Ge Yu; Guijie Xin; Xu Liu; Wanyu Li; Chen Shao; Runping Gao (Journal of Medical Case Reports)
Abstract Background Dyskeratosis congenita is a rare genetic disease due to telomere biology disorder and characterized by heterogeneous clinical manifestations and severe complications. “Porto-sinusoidal vascular disease” has been recently proposed, according to new diagnostic criteria, to replace the term “idiopathic non-cirrhotic portal hypertension.” TERT plays an important role in telomeric DNA repair and replication. A TERT c.2286 + 1G/A mutation in a splicing consensus site was identified in a patient with pulmonary fibrosis. Recently, a pathogenic de novo TERT c.280A > T variant was associated with diffuse lung disease in an infant. Case presentation A 16-year-old Han male patient experienced unexplained black stool for 7 days, accompanied by dizziness and fatigue. On examination, there were mesh pigmentations on the exposed areas of the skin on both hands and feet. Laboratory testing revealed moderate hemorrhagic anemia and mild elevation of alanine aminotransferase. A computed tomography scan showed portal hypertension, esophageal and gastric varices, and splenomegaly. The liver stiffness measurement by FibroScan was 6.0 kPa. Liver biopsy revealed typical features of porto-sinusoidal vascular disease. Whole exome sequencing identified a heterozygous TERT c.2286 + 1G > A de novo mutation and quantitative polymerase chain reaction revealed very short telomeres (less than the first percentile for his age). The patient was diagnosed as TERT de novo mutation-related dyskeratosis congenita and porto-sinusoidal vascular disease. He underwent esophageal and gastric variceal ligation treatment and received a carvedilol tablet (12.5 mg) every morning. After 6 months, he has moderate iron deficiency anemia and has started receiving polysaccharide iron complex therapy. Conclusion When discovering reticular rash and unknown portal hypertension, it is necessary to perform whole exome sequencing and chromosome length testing to clarify the possibility of dyskeratosis congenita/telomere biology disorder with porto-sinusoidal vascular disease.